The Influence of Customer Perception, Brand Fit, and Brand Credibility on Brand Image: A Case Study of Naming Rights of BT Batik Trusmi - Jihan Rhaudhatul Jannah; Ramlah Puji Astuti; Tiara Muthiarsih (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2026)
This study examines the influence of customer perception, brand fit, and brand credibility on BT Batik Trusmi's brand image in the case of the cancellation of the